Fatigue measured in dynamic versus isometric modes after trail running races of various distances - Koral, J.; Fanget, M.; Imbert, L.; Besson, T.; Kennouche, D.; Parent, A.; Foschia, C.; Rossi, J.; Millet, G. Y. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Fatigue has previously been investigated in trail running by comparing maximal isometric force before and after the race. Isometric contractions may not entirely reflect fatigue-induced changes, and therefore dynamic evaluation is warranted. The aim of the present study was to compare the magnitude of the decrement of maximal isometric force versus maximal power, force, and velocity after trail running races ranging from 40 to 170 km.